Synthesis of chitosan/zinc oxide nanoparticles stabilized by chitosan via microwave heating - Nurul Amira, Ahmad Yusof; Norashikin, Mat Zain; Norlin, Pauzi (Department of Chemical Engineering, Diponegoro University, 2019)
Nowadays, zinc oxide (ZnO) has attracted attention in research and development because of its remarkable antibacterial properties. Chitosan/ZnO nanoparticles were successfully synthesized via microwave heating. The objectives of this work were to investigate the effect of stabilizer, power heating and time heating on size of chitosan/ZnO nanoparticles and to determine antibacterial activity against pathogenic bacteria, where chitosan was used as a stabilizing agent. Chitosan/ZnO nanoparticles were analyzed by Fourier Transform Infra Red (FTIR), X-ray Diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), and Zetasizer instrument. The power heating and time heating were varied from 400 to 800 Watt and 4 to 8 minutes, respectively. The presence of chitosan has role on preventing the nanoparticles from agglomeration by producing a milky solution of chitosan/ZnO nanoparticles without any suspensions. The increase of power and time heating improved the size of nanoparticles. The peak in FTIR spectrum at around 427 cm-1 was confirmed the existence of the ZnO phase. XRD patterns showed that the chitosan/ZnO nanoparticles materials were pure phase with average crystalline size is 130 nm. FESEM revealed that chitosan/ZnO nanoparticles were uniformly distributed with the mean value of size is 70 nm and spherical shaped. Further impact of power and time heating on the size of the chitosan/ZnO nanoparticles can be shown by a nanoparticles size distribution with the average of 30 to 90 nm. The results showed that chitosan/ZnO nanoparticles have displayed an antibacterial inhibition zone against Gram-positive S. aureus and Gram-negative E. coli which 16.0 and 13.3 mm, respectively. Chitosan/ZnO nanoparticles were synthesized in this work presented have potential application to prevent bacterial infections.